2017
DOI: 10.1590/0001-3765201720160433
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of the reef-building Petaloconchus varians (Gastropoda: Vermetidae) on intertidal rocky shores at Ilha Grande Bay, southeastern Brazil

Abstract: The reef-building vermetid Petaloconchus varians occurs in the western Atlantic Ocean, from the Caribbean Sea to the southern coast of Brazil. The present study evaluated the abundance of P. varians on intertidal rocky shores in Ilha Grande Bay (Rio de Janeiro State), and characterized their reefs, describing the species density, besides the weight and the belt width of the reefs. Petaloconchus varians reefs were recorded at 25 sites, with rocky shores exposed to different wave action (very sheltered, sheltere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…A small, concave operculum is characteristic for the genus Petaloconchus H.C. Lea, 1843 [24]. Owing to its symbiotic nature, the coral-dwelling worm snail of the present study cannot be confused with previously reported Caribbean species, such as the reef-building Petaloconchus varians (d'Orbigny, 1839) in Venezuela [5] and Brazil [25]. The invasive vermetid Eualetes tulipa (Chenu, 1843) has also been recorded in the West Atlantic and the Caribbean, but its operculum is much darker than that of our specimens and it has not been reported as a coral symbiont but as colonies on rock and artificial substrate [26,27].…”
Section: Resultsmentioning
confidence: 61%
“…A small, concave operculum is characteristic for the genus Petaloconchus H.C. Lea, 1843 [24]. Owing to its symbiotic nature, the coral-dwelling worm snail of the present study cannot be confused with previously reported Caribbean species, such as the reef-building Petaloconchus varians (d'Orbigny, 1839) in Venezuela [5] and Brazil [25]. The invasive vermetid Eualetes tulipa (Chenu, 1843) has also been recorded in the West Atlantic and the Caribbean, but its operculum is much darker than that of our specimens and it has not been reported as a coral symbiont but as colonies on rock and artificial substrate [26,27].…”
Section: Resultsmentioning
confidence: 61%
“…According to Laborel (1986), vermetid populations disappear or decrease on the rocky coasts south of Cabo Frio, Rio de Janeiro. However, the occurrence of P. varians elsewhere in southeastern Brazil, at the Anjos cove in Arraial do Cabo and at the Ilha Grande Bay, further south, both in Rio de Janeiro State is well documented (Spotorno-Oliveira et al, 2016;Breves-Ramos et al, 2017). P. varians fossil assemblages were identified from the lower middle to the upper middle coastal zone (Spotorno-Oliveira et al, 2016).…”
Section: Vermetids and Barnacles As Sea-level Indicatormentioning
confidence: 97%